Pengaruh Gila Marketing, Inovasi Produk, Dan Minat Beli Terhadap Omset Penjualan Lilin Aromaterapi Di Surabaya - Priskila Evania Eraristy; Devita Diyan Putri Cahyaningtyas; Varrell Fernanda Maesa Ayu; Irnandhera Talitha Zadhah; Arman Raihan Shahruk Ardiansyah; Nindya Kartika Kusmayati (Faculty of Social and Political Science, 2025)
This study aims to examine the effect of Gila Marketing and product innovation on purchase intention and their impact on the sales turnover of aromatherapy candles in Surabaya. The research employed a quantitative approach with a survey method involving 93 respondents who had purchased aromatherapy candle products. Data were collected using structured questionnaires measured on a Likert scale. The collected data were analyzed using multiple linear regression with the assistance of SPSS to test both partial and simultaneous effects among variables. The results indicate that Gila Marketing has a positive and significant effect on sales turnover, while product innovation does not have a significant effect. Purchase intention also shows a positive and significant influence on sales turnover and is identified as the most dominant variable in the regression model. The regression equation obtained is Y = 0.271 + 0.368X1 + 0.144X2 + 0.462X3 + e, which demonstrates that an increase in purchase intention contributes more strongly to sales turnover compared to other variables. These findings confirm that creative and unconventional marketing strategies are effective in stimulating consumer purchase intention, which subsequently enhances sales performance. Conversely, product innovation does not directly influence sales turnover, indicating that consumers place greater emphasis on product functionality, scent quality, and usability rather than design innovation. Overall, the study highlights that the integration of effective marketing strategies and strengthened consumer purchase intention plays a critical role in improving sales turnover, while product innovation functions as a supporting factor for long-term competitiveness in the aromatherapy candle market.